PS-081 Monitoring key performance indicators on pharmaceutical validation: feedback over a million prescriptions in a general hospital. (25th February 2017) - Grimaux, J; Grosse, PY; Wereszczynski, N; Bertrand, B
Abstract : Background: Computerisation of medical prescriptions in our hospital began on 2006 and reached 100% in 2013 with complete pharmaceutical analysis. The activity indicators are monitored on a monthly basis. Purpose: The objective was to analyse the evolution of our practices over the past 6 years on more than 1 million prescriptions. The study focused on the impact of pharmaceutical interventions (PIs), their relevance and their consideration. Material and methods: From January 2010 to June 2016, key performance indicators on pharmaceutical validation were monitored on a monthly basis (number of prescriptions, prescription and validation schedules, number of PI and their consideration). Indicators were retrospectively analysed via prescription software (Dxcare, Medasys). Results: Over the study period, 1 080 115 prescriptions were validated. In the first quarter of 2016, it represented 763 lines of prescription per day. Pharmaceutical validation was made in real time: the schedules of prescriptions and pharmaceutical validation were similar. The percentage of PIs made by pharmacists did not stop decreasing over 6 years: 9.2% in 2010 versus 3.9% at the end of the first quarter of 2016. In the same way, the percentage of pharmaceutical refusals decreased by a factor of 2 between 2010 and 2016 (respectively, 4.1% and 2.1%). However, the period of time between the transmission of a PI by the pharmacist and the physician reaction hardly evolved. For instance, in 2016, 42% of PIs were taken into account within the first 24 hours that followed their establishment against 36% in 2010. Nevertheless, this observation also depended on the therapeutic class. A study carried out in the hospital on the appropriate use of direct oral anticoagulants (DOA) revealed that 73% of the PIs established for the DOAs in 2016 were taken into account within the first 24 hours, against 40% in 2014. Conclusion: Through the computerisation of prescriptions, pharmaceutical analysis and transmission of PIs can be facilitated. The actions carried out by the pharmacists greatly improved the accuracy of prescriptions by raising awareness of the physicians about proper use of drugs, in particular therapeutic classes at risk. No conflict of interest